ANALISIS KETIMPANGAN PEMBANGUNAN DAERAH SERTA HUBUNGANNYA DENGAN KESEJAHTERAAN MASYARAKAT DI KAWASAN GERBANGKERTOSUSILA PROVINSI JAWA TIMUR - FITRIYAH, LAILATUL (Jurnal Pendidikan Ekonomi (JUPE), 2013)
The problem of imbalance income is one of important problem in region economic development at sector GERBANGKERTASUSILA, East Java Province. The purpose of this research was to know the overview of GRDP of regency/city, analyzing imbalance level of income and it correlation with residents prosperity and find where sector giving more contribution for GRDP at year 2007-2011. Data used in this research was secondary data and method of collecting data used was documentation method. Analysis tool used to know the overview of GRDP and sector contribution was descriptive analysis. While to know the imbalance level of income used Williamson Index. Result of this research shows that GRDP of regency/city sustaining improvement annually. The imbalance income at sector GERBANGKERTASUSILA classified as high (close to 1) and tends to increased annually. Regency/city which has lower imbalance income with better prosperity level was Gresik Regency, Mojokerto Regency, Mojokerto City, and Sidoarjo Regency. Whereas regency/city has moderate imbalance income with middle-low prosperity was Bangkalan Regency. Regency/city sectors contribution dominated by commerce sector and processing industry sector. Keywords: GRDP, imbalance income, sector contribution